STUDY ON CHARACTERISTICS OF SEROLOGICAL DIAGNOSTIC RESULTS OF PARASITES IN PATIENTS WITH CHRONIC URTICARIA AT HO CHI MINH CITY HOSPITAL OF DERMATO-VERENEOLOGY (Vietnam Journal of Community Medicine, 2024)
Objective: To investigate diagnostic serology for Toxocara spp., Gnathostoma spp., Strongyloides stercoralis, Entamoeba histolytica, and Fasciola spp. in patients with chronic urticaria at Ho Chi Minh City Hospital of Dermato-Vereneology.Subjects and Methods: A case series descriptive study was conducted on 60 patients with chronic urticaria who were examined and treated at Ho Chi Minh City Hospital of Dermato-Vereneology. The study period was carried out from Oct 2016 to April 2017.Results: The positive rate of serology for parasite diagnosis was 76.7%. The seropositive rate of each parasite: Toxocara spp. (63.3%); Gnathostoma spp. (3.3%); Strongyloides stercoralis (16.7%); Entamoeba histolytica (3.3%); Fasciola spp. (13.3%). The ratio of positive diagnostic serotypes for the number of parasites was: 1 type (56.7%); 2 types (16.7%); 3 types (3.3%); No patient tested positive for 4 or 5 types of parasites simultaneously.Conclusion: The seropositivity rate for parasites in patients with chronic urticaria was relatively high, the highest with Toxocara spp.
Keywords: Diagnostic serum, parasites, chronic urticaria, Ho Chi Minh City Hospital of Dermato- Vereneology.